Legal Safeguards for Government Criticism Expression on Social Media Platforms Under the 2016 Information and Electronic Transactions Law (Law No. 19/2016) - Bimoribowo, Amadeus Yves; Azis, Rizka Amelia (Yayasan Kawanad, 2025)
Advances in information technology in the digital era have given rise to social media as a new means for people to voice their opinions, including criticizing the government. However, this freedom of expression often conflicts with legal aspects, particularly the provisions of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), which was amended by Law Number 19 of 2016, specifically Article 27 paragraph (3) and Article 28 paragraph (2). This research aims to examine how these two articles are implemented in responding to criticism of the government conveyed through social media and the extent to which legal protection is provided to citizens. The focus of the research was directed toward the case of Bima Yudho Saputro, who was reported for criticizing conditions in his home region through TikTok. This research adopts a normative juridical method with an analytical approach to legal and case research. The findings suggest that these articles are often misinterpreted and risk criminalizing legally valid forms of criticism, despite not fulfilling the elements of a crime. Legal protection, both preventive and repressive, remains ineffective due to weak regulations, insufficient understanding among law enforcement officials, and limited public access to legal aid. Therefore, regulatory reform and institutional strengthening are needed to ensure that freedom of expression remains protected within a democratic, rule-of-law system.